Discourses on Violence in Costa Rica, El Salvador, and Nicaragua: Laws and the Construction of Drug- and Gender-Related Violence - Peter Peetz (German Institute of Global and Area Studies (GIGA), 2008)
In Central America, legislation aiming to reduce violence and crime has become an important topic in the security debate. Focusing on Costa Rica, El Salvador, and Nicaragua, this paper analyzes laws and other legal texts regarding the trade in and consumption of drugs on the one hand, and gender-related violence on the other. It shows how the content and the wording of legal texts contribute to the social construction of stereotyped offenders, such as youth gang members, drug users, or foreign nationals. The legal texts in Costa Rica, El Salvador, and Nicaragua reflect both the hegemonic and the counter-discursive influences on each country's legal discourse. – – In Zentralamerika sind Gesetze, die Gewalt und Kriminalität verringern sollen, ein wichtiges Thema innerhalb der Sicherheitsdebatte. In diesem Working Paper werden Gesetze und andere juristische Texte aus Costa Rica, El Salvador und Nicaragua analysiert, in denen es entweder um Drogenhandel und -konsum oder um geschlechtsbezogene Gewalt geht. Es wird gezeigt, wie Inhalt und Wortwahl solcher Texte zur sozialen Konstruktion stereotyper Tätergruppen beitragen, bei denen es sich z.B. um die Mitglieder von Jugendbanden, um Drogenkonsumenten oder Ausländer handeln kann. In costaricanischen, salvadorianischen und nicaraguanischen Gesetzestexten spiegeln sich die Einflüsse wider, die sowohl der hegemoniale Diskurs als auch Gegendiskurse über Gewalt und Kriminalität auf den rechtlichen Diskurs haben.
Keywords: 300; Central America; violence; drugs; gender; legal discourse